Multivitamin supplementation as a potential adjunctive therapy in post-cardiac arrest: insights from a multicenter retrospective analysis of MIMIC-IV and eICU-CRD - Shen, Jiahao; Wang, Danjun; Zhao, Wenxuan; Que, Jun; Qian, Junwei; Zhang, Xiaoyun (Frontiers in Nutrition, 2025)
BackgroundCardiac arrest (CA) remains a global health challenge, with low survival rates despite advances in resuscitation. There is a need for novel therapies to improve post-resuscitation outcomes, and the potential role of multivitamin supplementation in this context remains underexplored.MethodsThis multi-center, retrospective observational study examined the association between multivitamin supplementation and clinical outcomes in CA patients. Data were derived from two publicly available critical care databases: the Medical Information Mart for Intensive Care IV (MIMIC-IV) as the training cohort and the eICU Collaborative Research Database (eICU-CRD) as the validation cohort. Adult CA patients were identified and categorized based on whether they received multivitamin supplementation during hospitalization. The primary outcome was in-hospital mortality, with ICU and 28-day mortality as secondary outcomes. Kaplan–Meier survival analysis, propensity score matching (PSM), and inverse probability treatment weighting (IPTW) were used to adjust for confounding variables. A stepwise Cox proportional hazards model evaluated the association between multivitamin use and mortality. Subgroup analyses were conducted based on age, gender, disease severity scores, and comorbidities. Stratified analyses were also performed for patients hospitalized ≥5 days, comparing outcomes between those receiving multivitamins for <5 days vs. ≥5 days.ResultsIn the MIMIC-IV cohort, 223 patients received multivitamins and 890 did not; in the eICU-CRD cohort, 174 received multivitamins and 2,455 did not. Patients receiving multivitamin supplementation had significantly higher survival rates for both in-hospital and 28-day mortality (p < 0.01). After PSM and IPTW adjustment, multivitamin use remained significantly associated with lower mortality in both cohorts. In the fully adjusted Cox model, hazard ratios for in-hospital mortality were 0.56 (95% CIs: 0.45–0.70), 0.47 (95% CIs: 0.35–0.62), and 0.52 (95% CIs: 0.42–0.65) in the original, PSM, and IPTW analyses, respectively (all p < 0.01). Subgroup analysis showed stronger effects in patients aged <65 years. Prolonged supplementation (≥5 days) was linked to better survival.ConclusionAcross two large critical care cohorts, multivitamin supplementation was associated with lower mortality after adjustment, consistent with a potential adjunctive role in post-cardiac arrest care.